MANAJEMEN BOARDING SCHOOL DI SMAIT AL-FITYAN KUBU RAYA DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU - Masrupah, Masrupah; Wicaksono, Luhur; Junanto, Tulus; Radiana, Usman; Rosnija, Eni (Jurnal Visi Ilmu Pendidikan, 2024)
This research aims to describe the function of boarding school management in the aspects of planning, organizing, monitoring and reporting in improving the pedagogical competence of teachers at SMAIT Al-Fityan Kubu Raya.Data collection methods are interviews, observation and documentation. Analysis model with data reduction, data presentation and drawing conclusions.The research findings of boarding school management at SMAIT Al-Fityan Kubu Raya in aspect 1) planning show that the annual work plan and financing plan are the implementation of the institution's vision, mission and objectives containing efforts to increase teacher pedagogical competence. 2) The organizational aspect is that the Institution has an organizational structure, a Decree and a schedule of activity programs that describes efforts to increase teacher pedagogical competence. 3) Controlling includes routine monitoring and evaluation activities 4) Reporting aspects in the form of activity and financial reports which are made routinely after activities are completed and submitted to related parties                   Keywords: Total Quality Management, School Quality    AbstrakPenelitian ini bertujuan mendeskripsikan fungsi manajemen boarding school pada aspek perencanaan, pengorganisasian, pengawasan dan pelaporan dalam meningkatkan kompetensi pedagogik guru di SMAIT Al-Fityan Kubu Raya. Metode pengumpulan data dengan wawancara, observasi dan dokumentasi. Model analisis dengan reduksi data, penyajian data dan penarikan kesimpulan. Hasil temuan penelitian manajemen boarding school di SMAIT Al-Fityan Kubu Raya pada aspek 1) perencanaan terlihat bahwa rencana kerja tahunan beserta rencana pembiayaan merupakan implementasi visi, misi dan tujuan lembaga mengandung upaya peningkatan kompetensi pedagogik guru. 2) pengorganisasian bahwa lembaga memiliki struktur organisasi, Surat Keputusan serta terdapat jadual program kegiatan yang menggambarkan upaya peningkatan kompetensi pedagogik guru. 3) pengawasan terdapat kegiatan monitoring dan evaluasi yang rutin 4) pelaporan dalam bentuk laporan kegiatan dan keuangan yang dibuat secara rutin dan memiliki dokumentasi yang baik.Kata Kunci: Manajemen, Boarding School, Kompetensi Pedagogik